Comparison of PTEN expression in Hashimoto thyroiditis, follicular adenoma, papillary and follicular carcinomas (Annals of Medical Research, 2021)
None
Keywords: Hashimoto Thyroiditis; Follicular Adenom; Papillary Thyroid Carcinoma; Follicular Thyroid Carcinoma; PTEN.